Radiation measurements from polar and geosynchronous satellites - Vonder Haar, Thomas H., author; Kidder, Stanley Q., author; Hillger, Donald W., author; Ellis, James S., author; Department of Atmospheric Science, Colorado State University, publisher (Colorado State University. Libraries, 1978)
This is the Annual report for period 1 November 1976-31 October 1977 and the Final report, 10 October 1970-31 July 1978 for National Aeronatuics and Space Administratin grant NGR-06-002-102.
June 1978.
Keywords: Solar radiation -- Measurement; Satellite meteorology